2015
DOI: 10.1177/0148607115602885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Intravenous Potassium Dosing Algorithm for Hypokalemic Critically Ill Patients

Abstract: Purpose: The intent of this study was to evaluate the safety and efficacy of an intravenous (IV) potassium (K) dosing algorithm for hypokalemic critically ill trauma patients. Methods: Adult patients, admitted to the trauma intensive care unit from June 2010 to October 2012 and who received IV K therapy according to a standardized dosing algorithm, were retrospectively evaluated. Patients who received IV K during resuscitation or following initiation of nutrition therapy, IV fluids containing >20 mEq/L of pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…This was the same as Amirnovin et al (2018), [37] Johnston et al (2017) [38] Scotto et al (2014), [39] Couture et al (2013), [33] Kanji and Jung (2009), [35] Owen et al (2008) [40] and Hijazi and Al-Ansari (2005) [13] findings. On the other hand, Zielenski et al (2017) [41] reported that timed, electronic, assessment-driven potassium-replacement protocol (TARP) improved the effectiveness and safety of potassiumreplacement therapy over the traditional NDERP without negatively affecting timeliness of care.…”
Section: Discussionsupporting
confidence: 79%
“…This was the same as Amirnovin et al (2018), [37] Johnston et al (2017) [38] Scotto et al (2014), [39] Couture et al (2013), [33] Kanji and Jung (2009), [35] Owen et al (2008) [40] and Hijazi and Al-Ansari (2005) [13] findings. On the other hand, Zielenski et al (2017) [41] reported that timed, electronic, assessment-driven potassium-replacement protocol (TARP) improved the effectiveness and safety of potassiumreplacement therapy over the traditional NDERP without negatively affecting timeliness of care.…”
Section: Discussionsupporting
confidence: 79%
“…The high incidence of ARC among critically ill patients with severe traumatic injuries in our study indicates marked potential for therapeutic underdosing of medications, electrolytes, and nutrients that are renally eliminated. The high prevalence of ARC among our patients with traumatic injuries may partially explain the requirement for aggressive intravenous electrolyte dosing in the management of hypophosphatemia [ 14 , 15 , 20 ], hypokalemia [ 18 , 52 ], hypocalcemia [ 16 , 17 ], and hypomagnesemia [ 19 ]. Subtherapeutic serum concentrations of renally-eliminated antibiotics, due to the presence of ARC in critically ill patients with infections, may lead to therapeutic failures, infection recurrence, and multidrug resistant strains [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This wide variability may be explained by differences in the definition of ARC, patient populations, dosage of protein during nutrition therapy, and timing of the observation relative to intensive care unit (ICU) admission. The unanticipated presence of ARC could lead to the inability to achieve normal serum electrolyte concentrations with conventional electrolyte dosing [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], suboptimal dosing of beta-lactam antibiotic therapy during serious infections [ 12 , 21 ], or ineffective dosing for other renally-eliminated drugs or nutrients that cannot routinely be pharmacokinetically adjusted. The primary objective of this study was to ascertain the incidence of ARC for critically ill patients with severe traumatic injuries who require enteral or parenteral nutrition therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Severe hypokalemia has historically been implicated via case series and case reports as a cause for paralytic ileus, 29 although this association has been questioned 30 . The NSS and primary trauma service are vigilant in evaluating serum potassium concentrations, 31 as is evidenced by the maintenance of serum potassium concentrations between 3.6 and 4.2 mEq/L for the tolerant and intolerant groups, respectively ( P = 0.298; Table 3). Thus, the serum potassium concentration was not associated with differences in gastric feeding tolerance between groups.…”
Section: Discussionmentioning
confidence: 99%